The Role of Strategic Leadership in the adoption of Talent Management Practices Field research in the Ministry of Science and Technology - سعيد, هديل كاظم; كاطع, افتخار عبد الحسين (Journal of Economics and Administrative Sciences, 2016)
The current research aims at testing test the relationship and the impact of strategic leadership (strategic vision, Core competencies , human capital, organizational culture and Ethical practices) in the talent management (to attract talent, performance management talent, developing talent and retain talent) among managers in the Ministry of Science and Technology Iraq, and figuring out  a number of recommendations to the ministry to help achieve its desired objectives, and to clarify the relationship between the variables to find the main and secondary aim of the research two major hypotheses have been formed which split into ten sub-hypotheses. Collecting data on  a form questionnaire has been relied on as an essential tool, which has been distributed to a sample search of number (74) directors in the Ministry  of Science and Technology..    All forms were submitted to the statistical analysis using SPSS program basing on a group of selected statistical means to study the relationship, the impact by the mean, standard deviation, coefficient of variation, spearman correlation, simple regression coefficient.    The research arrived at a collection of results, perhaps the most prominent of which were: there was a significant correlation  between the  strategic leadership and management talent, as it turned out that there is a significant effect of strategic leadership in the practice of  talent management, and that the level of influence is increasing their presence together which shows the outstanding role played by the dimensions of strategic leadership and its role in the ministry researched towards the adoption of talent management practices